Effectiveness of an adaptive, multifaceted intervention to enhance care for patients with complex multimorbidity in general practice: protocol for a pragmatic cluster randomised controlled trial (the MM600 trial) - Per Kallestrup; Anne Frølich; Frans Boch Waldorff; Susanne Reventlow; Volkert Siersma; Anne Møller; Dagný Rós Nicolaisdóttir; Janus Laust Thomsen; Tora Grauers Willadsen; Jesper Bo Nielsen; Line Bjørnskov Pedersen; Henrik Larsen; et al. (BMJ Open, 2024)
Introduction Patients with complex multimorbidity face a high treatment burden and frequently have low quality of life. General practice is the key organisational setting in terms of offering people with complex multimorbidity integrated, longitudinal, patient-centred care. This protocol describes a pragmatic cluster randomised controlled trial to evaluate the effectiveness of an adaptive, multifaceted intervention in general practice for patients with complex multimorbidity.Methods and analysis In this study, 250 recruited general practices will be randomly assigned 1:1 to either the intervention or control group. The eligible population are adult patients with two or more chronic conditions, at least one contact with secondary care within the last year, taking at least five repeat prescription drugs, living independently, who experience significant problems with their life and health due to their multimorbidity. During 2023 and 2024, intervention practices are financially incentivised to provide an extended consultation based on a patient-centred framework to eligible patients. Control practices continue care as usual. The primary outcome is need-based quality of life. Outcomes will be evaluated using linear and logistic regression models, with clustering considered. The analysis will be performed as intention to treat. In addition, a process evaluation will be carried out and reported elsewhere.Ethics and dissemination The trial will be conducted in compliance with the protocol, the Helsinki Declaration in its most recent form and good clinical practice recommendations, as well as the regulation for informed consent. The study was submitted to the Danish Capital Region Ethical Committee (ref: H-22041229). As defined by Section 2 of the Danish Act on Research Ethics in Research Projects, this project does not constitute a health research project but is considered a quality improvement project that does not require formal ethical approval. All results from the study (whether positive, negative or inconclusive) will be published in peer-reviewed journals.Trial registration number NCT05676541.